Effects of ZnO nanoparticles on the microstructure, mechanical properties and wettability of polypyrrole–polydopamine nanocomposites coated on W substrate. (September 2021) - Huang, Zhixiang; Pan, Chunyang; Huang, Panling; Si, Pengchao; Wu, Wenhao; Xu, Changfeng; Zhou, Jun; Li, Xueen
Abstract: Polypyrrole–polydopamine (PPy–PDA) coatings were fabricated on the surface of tungsten substrates based on fusion two different methods, electropolymerization and auto-polymerization, and ZnO nanoparticles (NPs) were simultaneously introduced to alleviate the mechanical mismatch between the brain tissue and conductive coating. The effects of ZnO NPs on microstructure, mechanical properties, adhesion strength, conductivity, and wettability of the nanocomposite coatings were systematically investigated. It resulted that the amorphous diffraction characteristics of PPy matrix polymer were not changed after adding ZnO NPs. However, the deposited rate of the coating was increased and the structure became coarser and porous. With the increasing concentration of NPs in electrolyte, ranging from 0 to 0.7 g/L, the elastic modulus and nano-hardness of the coating effectively reduced by 57% and 63%, respectively. However, the conductivity and adhesion strength were also decreased to a certain degree. Additionally, although the wettability of the PPy matrix polymer was limitedly influenced by the incorporation of ZnO NPs, it could be improved by 2 38% with the modification of PDA nano-film.